Novel germline mutations in the calreticulin gene: implications for the diagnosis of myeloproliferative neoplasms. Issue 11 (27th July 2016) - Szuber, Natasha; Lamontagne, Bruno; Busque, Lambert
Abstract : Mutations in the calreticulin (CALR) gene are found in the majority of Janus kinase 2-negative myeloproliferative neoplasms MPN and, thus far, have exclusively been reported as acquired, somatic mutations. We assessed the mutational status of exon 9 of the CALR gene in 2000 blood samples submitted to our centre and identified 12 subjects (0.6%) harbouring distinctive CALR mutations, all with an allelic frequency of 50% and all involving indels occurring as multiples of 3 bp. Buccal cell samples obtained from these patients confirmed the germline nature of the mutations. Importantly, these germline mutations were not diagnostic of MPN. We thus report for the first time the identification and confirmation of germline mutations in CALR distinct from those somatic mutations that define classical MPN. The finding of a non-standard CALR mutation with an allelic frequency of 50% should raise suspicion of the possibility of a germline CALR mutation and these cases investigated further.